Cost-effectiveness analysis of first-line treatments for recurrent or metastatic head and neck cancer in China: an economic evaluation based on network meta-analysis - Liu, Fen; Liu, Yuhang; Song, Guilin; Pan, Yong; Xia, Qiao; Li, Haonan (Frontiers in Pharmacology, 2025)
BackgroundRecurrent or metastatic head and neck squamous cell carcinoma (R/M HNSCC) is a common pathological type of head and neck tumors, imposing a huge disease burden in China. This study evaluated the cost-effectiveness of three first-line treatment regimens for R/M HNSCC approved in China from the perspective of Chinese payers, including cetuximab plus chemotherapy, pembrolizumab as monotherapy or in combination with chemotherapy, and finotonlimab plus chemotherapy, aiming to provide reference for decision-making.MethodsBased on the data from three randomized controlled trials: KEYNOTE-048 (NCT02358031), CHANGE-2 (NCT02383966), and the finotonlimab trial (NCT04146402), we conducted a network meta-analysis and employed partitioned survival model (PSM) to indirectly evaluate and compare the cost-effectiveness of treatments associated with finotonlimab, pembrolizumab (monotherapy or combination), and cetuximab. The simulation cycle of the model was set to 3 weeks, with a study duration of 20 years and a discount rate of 3.0%. The primary outcomes included life years (LYs), quality-adjusted life years (QALYs), incremental cost-effectiveness ratios (ICERs) and incremental net monetary benefits (INMBs), with a willingness-to-pay (WTP) threshold of 1–3 times China’s per capita gross domestic product (GDP). Furthermore, subgroup analyses, sensitivity analyses, and scenario analyses were performed to validate the robustness of the findings.ResultsIn the overall population, compared to cetuximab-chemotherapy, pembrolizumab monotherapy (ICER: 85,131.70/QALY) and pembrolizumab-chemotherapy (ICER: 203,545.22/QALY) were less cost-effective, while finotonlimab-chemotherapy (ICER: 161.13/QALY) was significantly more favorable. The net monetary benefit (NMB) analysis supported this finding, with finotonlimab-chemotherapy group having the highest INMB ($4,746.03 vs cetuximab-chemotherapy), followed by pembrolizumab (-$17,381.75) and pembrolizumab-chemotherapy (-$32,841.18). The results were similar in the population with PD-L1 CPS ≥1 and CPS ≥20. The one-way sensitivity analysis revealed that drug costs, the discount rate, and utility values for progression-free survival (PFS) and disease progression (PD) were key parameters significantly impacting the ICERs. Additionally, both probabilistic sensitivity analysis and scenario analysis confirmed that the results of base-case analysis were robust.ConclusionFrom the perspective of the Chinese population, finotonlimab-chemotherapy is the most cost-effective first-line treatment for R/M HNSCC, followed by cetuximab-chemotherapy. Pembrolizumab, whether as monotherapy or in combination, does not offer economic benefits.